In Vitro Infection with Hepatitis B Virus Using Differentiated Human Serum Culture of Huh7.5-NTCP Cells without Requiring Dimethyl Sulfoxide - Connie Le (Viruses, 2021)
An estimated two billion people worldwide have been infected with hepatitis B virus (HBV). Despite the high infectivity of HBV in vivo, a lack of easily infectable in vitro culture systems hinders studies of HBV. Overexpression of the sodium taurocholate co-transporting polypeptide (NTCP) bile acid transporter in hepatoma cells improved infection efficiency. We report here a hepatoma cell culture system that does not require dimethyl sulfoxide (DMSO) for HBV infection. We overexpressed NTCP in Huh7.5 cells and allowed these cells to differentiate in a medium supplemented with human serum (HS) instead of fetal bovine serum (FBS). We show that human serum culture enhanced HBV infection in Huh7.5-NTCP cells, e.g., in HS cultures, HBV pgRNA levels were increased by as much as 200-fold in comparison with FBS cultures and 19-fold in comparison with FBS+DMSO cultures. Human serum culture increased levels of hepatocyte differentiation markers, such as albumin secretion, in Huh7.5-NTCP cells to similar levels found in primary human hepatocytes. N-glycosylation of NTCP induced by culture in human serum may contribute to viral entry. Our study demonstrates an in vitro HBV infection of Huh7.5-NTCP cells without the use of potentially toxic DMSO.